Multiplexer Technology in Utility Automation - Levonen, Kimmo (My University, 2009)
In utility automation systems, data communication links have the essential role to convey real-time system between control centers and substations. Therefore, reliable and flexible communications are vital to run modern utility network in a safe and properly controlled way. In this thesis, possibilities of multiplexer technology in communications for utility automation systems are reviewed. At the beginning of this thesis, theory about multiplexing, especially SDH data transmission technology, and essential utility automation systems are discussed. Thereafter, the thesis concentrates on the characteristics and potential applications of the employer’s multiplexer device. Eventually, the performance requirements for the device are analyzed from the utility automation systems’ perspective and also some performance figures are measured with a build-up test system. Multiplexer technology was found to be well suitable for the underlying communications in utility automation systems. Especially the efficient protection schemes and network manageability makes SDH systems highly available and ensures quick reconfiguration in fault situations. Teleprotection that makes very fast operating times for power line protection possible, came up as the most important application.
Keywords: Multiplexer technology; utility automation; SDH; FOX515; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|